The UK’s kleptocracy problem: How servicing post-Soviet elites weakens the rule of law - Heathershaw, J; Cooley, A; Mayne, T; Michel, C; Prelec, T; Sharman, J; Soares de Oliveira, R (Chatham House, 2021)
The growth of London as a centre for financial and professional services coincided with the collapse of the USSR and the rise of post-Soviet kleptocracies in the 1990s. These states and their elites have since become a major source of clients for UK-based services firms and of investors in UK assets.